Visualizing the interaction between sodium caseinate and calcium alginate microgel particles. (January 2015) - Ching, Su Hung; Bhandari, Bhesh; Webb, Richard; Bansal, Nidhi
Abstract: In this study, the pH dependent adsorption of sodium caseinate onto the surface of micron-sized calcium alginate microgel particles (20–80 μm) was evaluated by electrophoretic mobility measurements (ζ-potential), microscopy, protein assay and a protein dye binding method. ζ-potential measurements and protein assay results suggested that protein adsorption occurred due to electrostatic complexation between sodium caseinate and calcium alginate and was pH dependent. Results of protein dye binding method were in agreement with those of protein assay and ζ-potential measurements. Confocal laser scanning and fluorescence microscopy confirmed the presence of protein layer on the surface of alginate microgel particles at pH 3 and 4. Micrographs from transmission electron microscopy revealed a protein coating with a thickness of ∼206–240 nm on the gel particle surfaces. Graphical abstract: Highlights: Caseinate–alginate microgel interaction was visualised with microscopy techniques. Caseinate adsorb onto alginate microgel particle through electrostatic interaction. The interaction of caseinate proteins with alginate gel particles was pH dependent. A dye-binding protein–alginate interaction detection method was described.